Intensi Berbasis PMT terhadap Kepatuhan Pengisian Dokumentasi Asuhan Keperawatan - Azhari, Indah; Krisnana, Ilya; Qur’aniati, Nuzul (Journal of Telenursing (JOTING), 2024)
This study aims to determine the influence of protection motivation theory (PMT)-based intentions on nursing care documentation compliance behavior. In this research, motivation that influences behavior is described by intention, which is an indication of how strongly someone wants to carry out a behavior. The method used in literature searches uses four databases, namely Google Scholar, PubMed, ProQuest, and ScienceDirect. Search for articles or journals using keywords and Boolean operators. The research results show that the most applicable benchmark for individual behavioral motivation in protection motivation theory is intention. The research conclusions illustrate that there is an intention showing a person's willingness to try to carry out behavior in accordance with applicable orders or policies. If the individual understands the risk of non-compliance in filling out nursing care documentation, then the individual will have the motivation to protect themselves (protection motivation) in the form of a desire to carry out documentation in accordance with the policy procedures that apply at the hospital. Keywords: intention, protection motivation theory, documentation of nursing care